Temptation, Resistance, and Art Objects: On the Lack of Material Theory within Art History before the Material Turn - Krispinsson, Charolotta (Artium Quaestiones, 2019)
Niccolò di Pietro Gerini's painting “The Temptation of Saint Anthony” (1390-1400) serves as a point of departure for this essay. It depicts Saint Anthony during a lapse of self-control as he attempts to resist an alluring mound of gold. Since the mound is in fact made of genuine gold leaves applied to the painting's surface, it works both as a representation of temptation as well as an object of desire affecting the beholder. The aim of this essay is to explore different approaches to materiality before the material turn within the art history discipline by examining two opposing directions within the writing and practice of art history: the tradition of connoisseurship; and the critique of the fetish within the theoretical apparatus of new art history and visual culture studies of the 1980s and 90s. As an expression of positivism within art history, it is argued that connoisseurship be considered within the context of its empirical practices dealing with objects. What is commonly described as the connoisseur's “taste” or “love for art” would then be just another way to describe the intimate relationship formed between art historians and the very objects under their scrutiny. More than other humanist disciplines, art history is, with the possible exception of archaeology, an object-based discipline. It is empirically anchored in the unruly, deep sea of objects commonly known as the history of art. Still, there has been a lack of in-depth theoretical reflection on the materiality of artworks in the writings of art historians before the material turn. The question however, is not ifthis is so, but rather, why? In this essay, it is suggested that the art history discipline has been marked by a complicated love-hate relationship with the materiality of which the very objects of study, more often than not, are made of; like Saint Anthony who is both attracted to and repelled by the shapeless mass of gold that Lucifer tempts him with. While connoisseurship represents attraction, resistance to the allure of objects can be traced to the habitual critique of fetishism of the first generations of visual culture studies and new art history. It reflects a negative stance towards objects and the material aspect of artworks, which enhanced a conceived dichotomy between thinking critically and analytically in contrast to managing documents and objects in archives and museum depositories. However, juxtaposing the act of thinking with the practice of manual labour has a long tradition in Western intellectual history. Furthermore, it is argued that art history cannot easily be compared to the history of other disciplines because of the simple fact that artworks are typically quite expensive and unique commodities, and as such, they provoke not just aesthetic but also fetishist responses. Thus, this desire to separate art history as a scientific discipline from the fetishism of the art market has had the paradoxical effect of causing art historians to shy away from developing methodologies and theory about materiality as an act of resistance.